Pengembangan E-Modul Berbasis Android Mata Kuliah Aplikasi Komputer sebagai Alternatif Pendukung Pembelajaran Jarak Jauh (PJJ) - Kurnia Wahyu Prima; Ganefri; Hansi Effendi; Remon Lapisa; Hariyadi (Jurnal Informasi dan Teknologi, 2022)
The current learning situation can be done by applying distance learning (PJJ). Technology is the key to sustainability in its implementation. Utilization of information technology in education, among others, can help during the learning process. Today, educators must keep abreast of the rapid development of technology and be able to use it more effectively to generate interesting teaching ideas. Learning media plays a very important role because it can help students in learning, especially in computer applications, or Aplikom for short. One of the learning media that can be used in utilizing technological developments is using an Android smartphone. With this, students can study independently anywhere and anytime. The purpose of this research is the development of android-based e-modules and to produce valid, practical and effective learning media in the Computer Applications course at the Muhammadiyah University of West Sumatra. The research method is the Research and Development (R&D) method using a 4D model. The 4D development procedure is Definition, Design, Development and Dissemination. Techniques in analyzing the data used are validity, practicality and effectiveness. The results obtained by the research are that the e-module that has been produced is valid with a media aspect value of 88% and a material aspect value of 93%. The e-module that has been produced is practically in accordance with the results of the lecturers' responses with a value of 97.3% and the results of student responses with a value of 88.3%. The resulting android-based e-module is effectively used with the postetst value of students' classical completeness which is 91% and the gain score value is 0.57 with a medium category. The conclusion is that the android-based e-modules produced are valid, practical and effective and useful in distance learning to help students learn independently.